2023
DOI: 10.3390/children10081395
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Moving School and Its Practical Implementation in Bavarian Higher Secondary Schools

Abstract: The roles of physical activity and the reduction in sedentary activities in the healthy physical, psychosocial and mental development of children and adolescents are undisputed. This is where the concept of Moving School comes in, which has been expanded to a holistic approach that takes into account all areas of the school, including lessons, after-school care and breaks, and aims to provide students with a sufficient level of physical activity. There are no current studies that show to what extent this conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Physical activity has wide-ranging benefits for children's physical and mental health [4]. Conversely, sedentary behavior (SB) exerts negative health consequences [5]. Advocates often emphasize the significance of engaging in PA for enhancement of academic achievement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical activity has wide-ranging benefits for children's physical and mental health [4]. Conversely, sedentary behavior (SB) exerts negative health consequences [5]. Advocates often emphasize the significance of engaging in PA for enhancement of academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity [13,14], poor metabolic health [15,16], and worse psychosocial health in children [5] have all been linked to voluminous SB. In a comprehensive, population-based survey, it was found that Americans between the ages of 8 and 18 years of age sat down for 10.7 h on average each day (11.2 h for boys and 10.3 h for girls).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation